Evaluation of road performance and carbon emission accounting analysis of recycled aggregates from construction and demolition waste - Xiaopei Duan; Yimin Wang; Duowang Yang; Wei Zeng; Yanqing Du; Ning Li (Scientific Reports)
Abstract This study deals with the problem of consumption of construction waste and shortage of traditional construction materials, offering a technical and environmental basis for the recycling and utilization of construction and demolition waste (CDW). Using waste concrete and waste bricks as recycled aggregates for pavement base materials, and cement, lime and fly ash as stabilizers, this study systematically explores the feasibility of stabilizing recycled aggregate-based materials for road use. The basic physical properties and macro-mechanical properties are analyzed, and the effects of stabilizer dosage (ESR), recycled aggregate dosage (RASR), and brick-concrete ratio (BCR) on the roadability of stabilized recycled aggregate materials are investigated. Revealing the significance and critical effects of multi-factors of strength development. Life cycle assessment (LCA) method is employed to measure the carbon emissions of different materials used as road pavement sub-base and compare them with those of natural aggregates. The results show that stabilized construction waste recycled aggregate is suitable for road subgrade. ESR, RASR and BCR have a significant effect on it with the order of BCR > RASR > ESR. The optimum ratio exists at 30% ~ 45% recycled aggregate blending and 1:2 of BCR. The carbon emission of cement stabilized class can be reduced from 60,789.66 to 48,117.03 kgCO2eq by using recycled construction waste aggregate instead of natural aggregate during construction period based on the base unit (a flow section length of 500 m as the basic unit), which is 19.2% reduction in carbon emission. For the lime fly ash stabilized category, the carbon emission is reduced from 53,246.65 to 41,734.03 kgCO2eq, which is 21.6% reduction in carbon emission. Recycled aggregates alone can achieve carbon emission reductions of 82.27%, 81.23%, and 78.02%, demonstrating a substantial environmental benefit in carbon reduction.